A case series on inflammatory cardiomyopathy and suspected cardiac sarcoidosis: role of cardiac PET in management. Issue 4 (3rd August 2020) - Kennel, Peter J; Raza, Farhan; Kim, Jiwon; Singh, Parmanand; Borczuk, Alain; Krishnan, Udhay; Karas, Maria; Sobol, Irina
Abstract: Background: Presentation of life-threatening arrhythmias concomitantly with a new-onset non-ischaemic cardiomyopathy raises concern for an inflammatory cardiomyopathy such as cardiac sarcoidosis or cardiac manifestations of connective tissue disease. Comprehensive workup for specific aetiologies may be unrevealing except for signs of myocardial inflammation identified on cardiac positron emission tomography (PET). Here, we present five cases of such subjects and their clinical course. Case summary: We collected clinical, imaging, pathological, and follow-up data of five subjects presenting with arrhythmias and unexplained new-onset cardiomyopathy. Mean age was 56.2 ± 5.8 years. Three subjects presented with ventricular tachycardia and two with atrial arrhythmias. Echocardiography showed a mean left ventricular ejection fraction of 37 ± 9%. Significant coronary artery disease was ruled out in all cases as the cause of the cardiomyopathy. All patients underwent cardiac magnetic resonance imaging (MRI) and PET scan at presentation and follow-up. In all patients, cardiac MRI revealed hyperenhancement in epicardial and mid-myocardial pattern in a non-coronary distribution, while PET scan revealed fluorodeoxyglucose (FDG) mismatch defects in multiple foci in a non-coronary distribution. Right ventricular biopsy was obtained in all patients and revealed interstitial fibrosis and cardiomyocyte hypertrophy. On median follow-up of 210 days, all subjects had improvement in both heart failure symptoms and arrhythmias and repeat PET in four out of five patients showed decreased inflammation. Discussion: A high level of suspicion for inflammatory cardiomyopathy is needed in patients presenting with new unexplained cardiomyopathy and arrhythmias. A cardiac FDG-PET should be considered for diagnosis if cardiac inflammation is in the differential. This can inform further decisions regarding targeted immunomodulation therapy that may be helpful in this cohort.